The Influence of Culturae on Innovarive Behaviour and Management in Singapore - C.M Yap; D.H Buisson; T.C Garrett (ASEAN Journal on Science and Technology for Development, 2000)
The Influence of Culturae on Innovarive Behaviour and Management in Singapore